Convex Conic Formulations of Robust Downlink Precoder Designs With Quality of Service Constraints - Shenouda, Michael Botros; Davidson, Timothy N. (IEEE journal of selected topics in signal processing, 2007)
We consider the design of linear precoders (beamformers) for broadcast channels with Quality of Service (QoS) constraints for each user, in scenarios with uncertain channel state information (CSI) at the transmitter. We consider a deterministically-bounded model for the channel uncertainty of each user, and our goal is to design a robust precoder that minimizes the total transmission power required to satisfy the users' QoS constraints for all channels within a specified uncertainty region around the transmitter's estimate of each user's channel. Since this problem is not known to be computationally tractable, we will derive three conservative design approaches that yield convex and computationally-efficient restrictions of the original design problem. The three approaches yield semidefinite program (SDP) formulations that offer different trade-offs between the degree of conservatism and the size of the SDP. We will also show how these conservative approaches can be used to derive efficiently-solvable quasi-convex restrictions of some related design problems, including the robust counterpart to the problem of maximizing the minimum signal-to-interference-plus-noise-ratio (SINR) subject to a given power constraint. Our simulation results indicate that in the presence of uncertain CSI the proposed approaches can satisfy the users' QoS requirements for a significantly larger set of uncertainties than existing methods, and require less transmission power to do so.